2015
DOI: 10.1039/c5ra10016j
|View full text |Cite
|
Sign up to set email alerts
|

APTES mediated modular modification of regenerated silk fibroin in a water solution

Abstract: Silk fibroin (SF) is a natural polymer of increasing interest for applications ranging from tissue engineering to optoelectronics. Here, we report a new mild and facile strategy targeted on hydroxilic pendants of serine and tyrosine residues, to functionalize SF in water, based on the use of amino(propyl)triethoxysilane (APTES) a common sililating agent. APTES is exploited as bifunctional linker to bind SF through the triethoxysilane α-ends and to simultaneously graft species of interest, even hydrophobic ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…In this view, analyses and comparison of samples obtained by blending and addition to SF solution of the selected compound with samples obtained by doping diet method revealed that the sample obtained by doping diet method displays a similar efficiency of functionalization of the substrates. Moreover the method does not affect SF structural, chemophysical and biological property [14,24,27,28].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In this view, analyses and comparison of samples obtained by blending and addition to SF solution of the selected compound with samples obtained by doping diet method revealed that the sample obtained by doping diet method displays a similar efficiency of functionalization of the substrates. Moreover the method does not affect SF structural, chemophysical and biological property [14,24,27,28].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In recent years, silk fibroin has been eliciting ever-increasing interest in the biotechnology field. Several applications have been reported, spanning tissue engineering , to regenerative medicine, drug delivery to biophotonics, and implantable devices to the last frontiers in bioengineering and the realization of biodegradable, bioresorbable, and edible electronic devices. The main reason behind such a success story is the peculiar advantages offered by silk, in terms of outstanding mechanical properties, chemical–physical versatility due to its polymorphic character, thermal and environmental stability, suitability to several processing techniques (easily allowing for covering dimensions from the nano- to the macroscale), endless opportunities of functionalization with biomolecules and drugs, and excellent cytocompatibility. Overall, silk is widely recognized as a highly promising material platform, with global impact in the biomedical, biophotonics, and bioelectronics fields …”
Section: Introductionmentioning
confidence: 99%
“…The repetitive GAGAGX hexapeptide units (X = S, Y, or A), which form an antiparallel β-sheet structure, are the main component of SF and are essential for exhibiting high tensile strengths. Several attempts to modify the properties of SF and to add novel functions have been reported. For example, coupling reactions using cyanuric chloride, carbodiimide, glutaraldehyde, alkoxysilane, and isocyanate have been demonstrated, whereas the diazonium coupling chemistry was also applied in terms of the selective introduction of unnatural functional groups to the tyrosine residues. , Enzymatic modification is also an attractive approach because the highly selective modification of complicated compounds can be achieved under mild conditions. The introduction of poly­(2,6-di­methyl­ene­phenyl­ene ether) onto the side chain of SF via the grafting-from method using horseradish peroxidase as a catalyst has been developed in our group to impart hydrophobicity to silk materials, while Freddi and co-workers reported the tyrosinase-catalyzed modification of SF to graft the polysaccharide chitosan. , In addition, the fabrication of silk composites with other materials such as polymers and inorganics provided the desired properties. , The development of these approaches is significantly important because of the high potential for the practical use of silk-based materials.…”
Section: Introductionmentioning
confidence: 99%